The Moderating Effect of Inflation on the Relationship Between Return on Assets (ROA) and Stock Prices - Chandra Firmansyah; Acep Komara (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This paper aims to examine the influence of Return on Assets on stock prices and furthermore assess the role of inflation as a moderating variable in food and beverage sector companies listed on the Indonesia Stock Exchange from 2022 to 2024. The study applies a quantitative approach using secondary data from yearly corporate financial disclosures, closing stock prices, along with official inflation data from Statistics Indonesia and Bank Indonesia. The research demographic consists of 98 companies. After applying purposive sampling, 42 companies chosen to serve as the research specimen, obtaining 126 data points. The data analysis was conducted using Stata 17 through pooled data analysis and Moderated Regression Analysis. The model selection process involved certain diagnostic tests (the Chow, Hausman, and Lagrange Multiplier tests), while the final model was analyzed using a Random Effects approach. The results show that Return on Assets has a positive and significant effect on stock prices. This finding indicates that asset efficiency remains a financial signal evaluated by investors when assessing a company's prospects. However, inflation does not moderate the relationship between Return on Assets and stock prices at the 5 % significance threshold. This low R-squared value indicates that stock prices are not only influenced by profitability and inflation, but also by other factors such as capital structure, firm size, interest rates, stock liquidity, and market sentiment.